English Mediasi Penanganan Konflik Batas Wilayah Suku Dani dengan Suku Mee Kabupaten Nabire - Pamungkas Wicaksono; Mohamad Ikhwan Syahtaria; Herlina Juni Risma Saragih; Pujo Widodo; Achmed Sukendro (CV. AFDIFAL MAJU BERKAH, 2024)
This study discusses the implementation of mediation in handling territorial boundary conflicts between the Mee and Danoi tribes in Nabire Regency. Territorial boundary conflicts in Nabire have become a serious concern, leading to horizontal and social conflicts. Mediation is one of the best alternatives for conflict resolution. Therefore, this study aims to analyze the dynamics of the conflict and the mediation efforts carried out by the government and other stakeholders. The research method used is descriptive qualitative, with data collection from literature, the internet, and applicable legislation. The findings of this study indicate that this conflict is a social conflict affecting regional stability. However, the role of the government as a mediator is crucial in resolving land disputes. The mediator functions as a neutral party with experience, capability, and integrity in problem-solving. It is recommended that territorial boundaries be recognized as triggers for horizontal conflicts between communities. Therefore, it is suggested that local and regional governments coordinate to form a working team to issue a Regent or Regional Regulation on Village Boundary Determination in cooperation with local village and traditional authorities.